Relationship Between Humeral Energy Flow During the Baseball Pitch and Glenohumeral Stability - Barfield, Jeff W.; Wasserberger, Kyle W.; Oliver, Gretchen D. (International Journal of Sports Medicine, 2020)
Researchers suggest that motion deriving energy from the more proximal segments of the body is important to reduce injury susceptibility. However, limited clinical assessments have been associated with efficient energy flow within a complex movement such as the baseball pitch. This research aimed to determine the relationship between glenohumeral stability as determined by the closed kinetic chain upper extremity stability test and energy transfer into and out of the humerus during the baseball pitching motion. Kinematic and kinetic data were collected at 240 Hz on twenty-four baseball pitchers. Participants performed the closed kinetic chain upper extremity stability test prior to throwing three fastballs at game speed to a catcher with the fastest fastball used for analysis. Spearman’s Rho were used to examine relationships between energy flow in and out of the humerus with glenohumeral stability as determined by the average score and normalized stance width during the closed kinetic chain upper extremity stability test. There was a significant negative correlation between the average score and normalized peak power leaving the humerus (rs[22]=−0.42, p=0.04). This result provides preliminary support for the use of the closed kinetic chain upper extremity stability test as a clinical assessment of a pitcher’s ability to efficiently transfer energy within the upper extremity during the pitch.
Keywords: biomechanics; pitching; proximal stability; stability assessment